(untitled) (Libellarium: časopis za istraživanja u području informacijskih i srodnih znanosti, 2017)
This study has provided insights into the activities of members of the Facebook heritage group “Zagreb kakav je bio nekada” that can support the creation of the old Zagreb image collection and the building of the user community around this collection. We have used historical and content analysis to examine the relationships between the characteristics of images posted in this group and activities of its members. Based on the findings from this research, we have made recommendations to the creators of digital libraries which could help them plan and build better participative digital libraries and their user communities. We hope that the insights obtained by this research as well as the novel methodological approach used in this study will be valuable as a foundation for further research.